Character Education Based Curriculum Management Through SKU (Ubudiyah Proficiency Standard) at Madrasah QITA Malang - Kamilatul Ubudiyah; Rachmad Ramadhan; Eric Mesry (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to describe the management of a character education-based curriculum through SKU (Ubudiyah Proficiency Standart) at Madrasah QITA Malang. This type of research includes qualitative descriptive research or is often also called a case study because this research describes an event or event that occurred in the field. Data collection techniques obtained through observation, interviews, and documentation. Based on the results of the study that: first, it was explained that the management of a character education-based curriculum through SKU (Ubudiyah Proficiency Standart) went well according to standards through four stages, namely in terms of Planning, Organizing, Driving and Evaluating. This aims to create students who have noble character and always obey the commands of Allah SWT without forgetting themselves as human beings. Secondly, the inhibiting factor in implementing SKU at QITA Madrasah is the existence of internal and external factors such as the lack of awareness of students or parents that the importance of SKU in everyday life. The solution that can be done to overcome these inhibiting factors is to first identify the causes or problems faced by students then report to parents on the problems experienced by students, provide sanctions related to religion and provide counseling guidance to solve problems.